Dun and Bradstreet's guide to doing business around the world - Morrison, Terri; Conaway, Wayne A.; Douress, Joseph J. (Englewood Cliffs, N.J. : Prentice Hall, 1997)
An alphabetical listing of 40 U.S. trade partners which gives trade information, risk ratings, political profiles, economic overview, vital statistics, and comparative ranking as a market for U.S. goods. The countries included are: Argentina, Australia, Belgium, Brazil, Canada, Chile, China, Colombia, Costa Rica, Czech Republic, Denmark, Egypt, England, France, Germany, Hong Kong, India, Indonesia, Ireland, Israel, Italy, Japan, Malaysia, Mexico, Netherlands, Peru, Philippines, Poland, Russia, Saudi Arabia, Singapore, South Africa, South Korea, Spain, Sweden, Switzerland, Taiwan, Thailand, Turkey, United Kingdom, Venezuela.
Argentina -- Australia -- Belgium -- Brazil -- Canada -- Chile -- China -- Colombia -- Costa Rica -- Czech Republic -- Denmark -- Egyp t-- England (included in United Kingdom) -- France -- Germany -- Hong Kong -- India -- Indonesia -- Ireland -- Israel -- Italy -- Japan -- Korea, South
Includes index.
Keywords: Export marketing -- Cross-cultural studies -- Handbooks, manuals, etc; International trade -- Cross-cultural studies -- Handbooks, manuals, etc; International business enterprises -- Cross-cultural studies -- Handbooks, manuals, etc; Intercultural communication -- Handbooks, manuals, etc